Wearable monitors criterion validity for energy expenditure in sedentary and light activities - Florez-Pregonero Alberto; Meckes Nathanael; Buman Mathew; Barbara E. Ainsworth (Elsevier, 2017)
Background: Wearable monitors (WMs) are used to estimate the time spent in sedentary behaviors (SBs) and light-intensity physical activities (LPAs) and their associated energy cost; however, the accuracy of WMs in measuring behaviors on the lower end of the intensity spectrum is unclear. The aim of this study was to assess the validity of 3 WMs (ActiGraph GT3X+; activPAL, and SenseWear 2) in estimating the intensity of SB and LPA in adults as compared with the criterion measure of oxygen uptake (VO2) measured by indirect calorimetry. Methods: Sixteen participants (age: 25.38 ± 8.58 years) wore the ActiGraph GT3X+, activPAL, and SenseWear 2 devices during 7 sedentary-to-light activities. VO2 (mL/kg/min) was estimated by means of a portable gas analyzer, Oxycon Mobile (Carefusion, Yorba Linda, CA, USA). All data were transformed into metabolic equivalents and analyzed using mean percentage error, equivalence plots, Bland-Altman plots, kappa statistics, and sensitivity/specificity. Results: Mean percentage error was lowest for the activPAL for SB (14.9%) and LPA (9.3%) compared with other WMs, which were >21.2%. None of the WMs fell within the equivalency range of ±10% of the criterion mean value. Bland-Altman plots revealed narrower levels of agreement with all WMs for SB than for LPA. Kappa statistics were low for all WMs, and sensitivity and specificity varied by WM type. Conclusion: None of the WMs tested in this study were equivalent with the criterion measure (VO2) in estimating sedentary-to-light activities; however, the activPAL had greater overall accuracy in measuring SB and LPA than did the ActiGraph and SenseWear 2 monitors.